2009
DOI: 10.1016/j.pmrj.2009.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Early Intra‐Articular Hip Disease Presenting With Posterior Pelvic and Groin Pain

Abstract: Twenty percent of patients at the authors' institution who required surgical intervention to treat their pain after not responding to conservative management had posterior pelvic pain in addition to groin or lateral and anterior hip pain. Of those respondents, 33% had complete resolution of symptoms at 4.75 years after surgery, and all had reduction in pain as compared with completion of conservative care. Patients with early intra-articular hip pathology, such as acetabular labral tears with no or mild hip de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 16 publications
0
34
0
1
Order By: Relevance
“…19 Similarly, 20% of patients with either labral tears or early hip joint degenerative changes experienced posterior hip pain. 20 Most of the patients with posterior hip pain in that study experienced concomitant anterior hip pain. 20 Sakamoto et al investigated regional pain patterns of the hip, both at rest and with motion, in patients with either hip OA or osteonecrosis and found that approximately 19% of these patients experienced posterior hip pain at rest and that 37% had posterior hip pain with motion.…”
Section: Femoroacetabular Joint Derangement (Ie Osteoarthritismentioning
confidence: 79%
See 1 more Smart Citation
“…19 Similarly, 20% of patients with either labral tears or early hip joint degenerative changes experienced posterior hip pain. 20 Most of the patients with posterior hip pain in that study experienced concomitant anterior hip pain. 20 Sakamoto et al investigated regional pain patterns of the hip, both at rest and with motion, in patients with either hip OA or osteonecrosis and found that approximately 19% of these patients experienced posterior hip pain at rest and that 37% had posterior hip pain with motion.…”
Section: Femoroacetabular Joint Derangement (Ie Osteoarthritismentioning
confidence: 79%
“…20 Most of the patients with posterior hip pain in that study experienced concomitant anterior hip pain. 20 Sakamoto et al investigated regional pain patterns of the hip, both at rest and with motion, in patients with either hip OA or osteonecrosis and found that approximately 19% of these patients experienced posterior hip pain at rest and that 37% had posterior hip pain with motion. 21 Evaluation of femoroacetabular OA and acetabular labral tears are discussed with anterior hip pain.…”
Section: Femoroacetabular Joint Derangement (Ie Osteoarthritismentioning
confidence: 79%
“…One study included only female participants,32 while two studies utilised athletic populations of male-only elite sports (United States (NHL), Australian Rules Football) 4 34. The remaining 26 studies had representation from both genders, with the percentage of women ranging from 25%33 to 61% 35. The mean age of individual cohorts ranged from 20 years36 to 47 years,37 while the overall mean age across all studies was 354 years.…”
Section: Resultsmentioning
confidence: 99%
“…The Harris Hip Score (HHS) includes an observer measure of the hip range of motion in addition to the PROs and was used in two studies 32 44. The most frequently used measure was the modified Harris Hip Score (MHHS) (21 studies),4 30 3335 40 4556 which was adapted from the HHS (physical range of motion measures removed). While the MHHS has construct validity for hip arthroscopy,42 its reliability has not been tested.…”
Section: Resultsmentioning
confidence: 99%
“…In a previous descriptive study, 20% of patients successfully treated with hip arthroscopy for acetabular labral tears in isolation with pain unresponsive to conservative treatment reported posterior pelvic pain as part of the distribution of pain before surgery. 9 In a series of descriptive studies, posterior pelvic pain was reported by patients before surgery in 17.3% of patients with DDH, 29% of patients with FAI, and 38% of patients with isolated acetabular labral tears. [10][11][12] Patients with FAI also reported a 23% incidence of low back pain and 12% incidence of posterior thigh pain.…”
Section: Historymentioning
confidence: 99%